The role of the Polochic Fault as part of the North American and Caribbean Plate boundary: Insights from the infill of the Lake Izabal Basin. (28th January 2020) - Obrist‐Farner, Jonathan; Eckert, Andreas; Locmelis, Marek; Crowley, James L.; Mota‐Vidaure, Byron; Lodolo, Emanuele; Rosenfeld, Joshua; Duarte, Edward
Abstract: The Lake Izabal Basin in Guatemala is a major pull‐apart basin along the sinistral Polochic Fault, which is part of the North American and Caribbean plate boundary. The basin infill contains information about the tectonic and sedimentological processes that have imparted a significant control on its sedimentary section. The inception of the basin has been linked to the relative importance of the Polochic Fault in the tectonic history of the plate boundary; yet, its sedimentological record and its inception age have been poorly documented. This study integrates diverse datasets, including industry reports, well logs and reports, well cuttings, vintage seismic data, outcrop observations and geochronological data to constrain the initial infill and age of inception of the basin. The integrated data show that during the Oligocene–Miocene, a marine carbonate platform was established in the region which was later uplifted and eroded in the early Miocene. The fluvial–lacustrine deposits above this carbonate platform are part of the initial infill of the basin and are constrained with zircon weighted‐mean 206 Pb/ 238 U ages of 12.060 ± 0.008 from a volcanic tuff ~30 m above the unconformity. Sandstone, mudstone and coal dominate the interval from 12 to 4 Ma, with an increase in conglomerate correlating to the uplift of the Mico Mountains and San Gil Hill at 4 Ma. Fault switch activity between the Polochic and Motagua faults has been hypothesized to explain total offset along the Polochic Fault and the geologic and geodetic slip rates along the two faults. The 12 Ma age determined for the initial infill of the basin confirms this hypothesis. Consequently, our study confirms that at ~12 Ma the Polochic Fault served as the main fault of the plate boundary with inferred slip rates ranging from 13 to 21 mm/yr with a strong possibility that the Polochic Fault was, at some point between 15 Ma and 7 Ma, the only active fault of the plate boundary. The results of this study show that tectonic records preserved in sediments of strike‐slip basins improve the understanding of the relative significance of individual faults and the implications with respect to strain partitioning throughout its tectonic history. Abstract : The Lake Izabal Basin initiated at 12 Ma. The Polochic Fault was the main plate boundary in the Miocene. Fault switch activity must have occurred along the plate boundary.